Exosomes: A novel insight into traditional Chinese medicine - Mo, Chao; Zhao, Jie; Liang, Jingyan; Wang, Huiling; Chen, Yu; Huang, Guodong (Frontiers in Pharmacology, 2022)
Exosomes are small extracellular vesicles and play an essential role in the mediation of intercellular communication both in health and disease. Traditional Chinese medicine (TCM) has historically been used to maintain human health and treat various diseases up till today. The interplay between exosomes and TCM has attracted researchers' growing attention. By integrating the available evidence, TCM formulas and compounds isolated from TCM as exosome modulators have beneficial effects on multiple disorders, such as tumors, kidney diseases, and hepatic disease, which may associate with inhibiting cells proliferation, anti-inflammation, anti-oxidation, and attenuating fibrosis. Exosomes, a natural delivery system, are essential in delivering compounds isolated from TCM to target cells or tissues. Moreover, exosomes may be the potential biomarkers for TCM syndromes, providing strategies for TCM treatment. These findings may provide a novel insight into TCM from exosomes and serve as evidence for better understanding and development of TCM.